Analisis Faktor yang Mempengaruhi Implementasi Standar Keselamatan Pasien - Marlina, Nina; Budiman, Budiman; Oyoh, Oyoh; Mulyati, Mulyati (Journal of Telenursing (JOTING), 2024)
This study explores the factors that can influence the implementation of patient safety standards. The method used is correlational analysis with a cross-sectional approach. The results of the study indicate that there is a significant partial effect of gender on the implementation of patient safety standards p-value of 0.005; there is a significant partial effect of education on the implementation of patient safety standards p-value of 0.011, meaning that there is a significant partial effect of length of service on the implementation of patient safety standards p value 0.037; there is a significant partial effect of awareness on the implementation of patient safety standards p value 0.001; compliance has a partial considerable impact on the implementation of patient safety standards p value 0.001. In conclusion, awareness is the dominant factor influencing the implementation of patient safety standards. Keywords: Nurse Compliance, Nursing Services, Patient Safety Standards